Prevalence of childhood cancer survivors in Europe: a scoping review - Neimar de Paula Silva; Andrea Gini; Anastasia Dolya; Murielle Colombet; Isabelle Soerjomataram; Danny Youlden; Charles Stiller; Eva Steliarova-Foucher; Joanne Aitken; Freddie Bray; Murielle Colombet; Neimar de Paula Silva; et al. (EJC Paediatric Oncology, 2024)
Childhood cancer survivors (CCS) require specialized follow-up throughout their lifespan to prevent or manage late effects of cancer treatment. Knowing the size and structure of the population of CCS is crucial to plan interventions. In this scoping review we reviewed studies that reported prevalence of CCS in Europe. We searched Medline, Web of Science, and Embase using permutations of terms referring to childhood, cancer, survivors, prevalence, registries, and Europe. We followed PRISMA-ScR guidelines to select studies and The Joanna Briggs Institute Prevalence Critical Appraisal Tool to evaluate their quality. From 979 unique studies published between 1989 and 2022, 12 were included. Limited-duration prevalence (LDP) for all childhood cancers, assessed in three studies using counting method, varied between 450 and 1240 persons per million. Complete prevalence (CP) of survivors of any childhood cancer except skin carcinomas, reported in three studies using observed data complemented with modelled data for the unobserved period, varied between 730 and 1110 persons per million. CP of survivors of an embryonal tumour was estimated by completeness index method in six studies. In four of them CP ranged from 48 to 95 persons per million for all embryonal tumours, while CP for those occurring in central nervous system was 43 per million in one study and CP for rhabdomyosarcoma was 17 per million in another. Information on prevalence of CCS in Europe is fragmented and inconsistent. The large variations in LDP and CP estimates were linked to differences in data availability, the selection of populations, prevalence measure, statistical method, incidence period, index date, age at diagnosis and prevalence, cancer types, sex, and, for LDP, also the length of follow-up. Standardisation of methodology and reporting are needed to systematically monitor and compare CCS prevalence in Europe and provide data to help address survivors’ needs.